The Dynamic Education and the Problems Rodamap Education in Indonesia - Fatahillah, Muhammad; Afadh, Muhammad (CV. Creative Tugu Pena, 2022)
This article reviewed the dynamics of education in indonesia and the problems roadmap education of 2020-2035 in Indonesia. The researchers have conducted a data collection series consisting of literature searching, observation, and documentation to prove this assumption. Furthermore, data was analyzed by defining the research question, collecting answers by sharpening the correlation and comparison between the questions and answers or findings. Finally, the researchers interpret in-depth whether the findings were valid and reliable. The design used phenomenology approach. The result showed that the education roadmap in Indonesia for 2020-2035 has indeed been made by a government agency, namely the Ministry of Education and Culture. However, it invites many question marks in various circles, both academics and society in general. This is due to the loss of religious phrases in it. Therefore, the government, especially the Ministry of Education and Culture should immediately revise and improve it so that it can be accepted by all parties Keywords: Problem Education Indonesia, Dynamic Education Indonesia, Indonesian Education